Računovodski izkazi in finančno poročanje - Jakopič, Breda (Mostovi (Ljubljana), 2006)
The financial statements are a special kind of accounting report by which the enterprises report to the external and internal users of accounting information. The purpose of accounting reporting is to provide information on financial position, financial performance, and cash flows of the enterprise. The enterprises report to their users in the annual reports that comprise the accounting report and the business report. The accounting report consists of the financial statements and the notes to the financial statements. The minimum scope of information to be disclosed is determined by the law and the accounting standards.
Keywords: angleščina; prevajanje; računovodsko poročanje; računovodstvo; slovenščina; terminologija